Persistent Doubts and Uncertainties of Evelyn’s Despair in Everything Everywhere All at Once Movie Script - Kirana, Kheista Sasi; Nurdin, Dewi Syifanaya Firdausy; Wijayanto, Bagus Pratama; Hizbullah, Akmal Dafa; Pasopati, Rommel Utungga (LPPM Universitas Pekalongan, 2025)
This article explores how the movie Everything Everywhere All at Once, written by Daniel Kwan and Daniel Scheinert, depicts existential despair through Evelyn Wang’s persistent doubts and uncertainties. As the story unfolds, Evelyn is thrown into the multiverse, where she encounters numerous versions of herself, overwhelming her with never-ending possibilities. These encounters lead her to question her choices, as well as her sense of purpose and self-worth. The ongoing uncertainty about which version of herself is “right” or “real” drives Evelyn into a state of existential despair, intensifying her feelings of hopelessness. By applying Kierkegaard’s theory of existential despair and qualitative method, this research analyzes how Evelyn’s internal conflict reflects the dread and disorientation that emerge when individuals face the uncertainty of their existence. In conclusion, through an examination of Evelyn’s perception of freedom and identity, also shaped by her doubts, the psychological and philosophical weight of uncertainty in the quest for authenticity and purpose are underscored further.